Rakyat Selayar Membela Indonesia: Sejarah Perlawanan Mempertahankan Kemerdekaan - Muhammad Hidayat Al Amin (Rayhan Intermedia, 2017)
This paper examines the societies of the late Japanese occupation in Selayar, the Selayar's form of resistance in facing the Allies and NICA, and the role of lasykar AMRIS and PPNI as a struggle organization that aims to embrace all elements of society from various villages to fight against the Allies and NICA. The research was conducted through field study and literature review with historical method of occupation: heuristics (source collection), verification, interpretation and historiography. The results show that the end of the Japanese occupation in Selayar in 1945, the situation of the Selayar people is getting worse. Needs such as food clothing are hard to find because Selayar's produce is used to finance the war against the Allies.on the other hand there is still an advantage to get the military training and this skill is used against the Dutch and Allied. Selayar people perform guerrilla strategy in the fight against the Dutch which originated from the capture of several leaders such as Rauf Rahman, Nastoera, Muh. Amin Solong, and Muh. Ali Solong. This opposition turned out to have been able to unite the people of Selayar in a container of struggle namely the Indonesian Selayar Youth Force (AMRIS) and the Selayar National Youth Center of Indonesia (PPNI). Both of these containers have become a means of cooperation and join in unity Lasykar Rebellion of the Republic of Indonesia (LAPRIS) and Guerilla Unity of South Sulawesi (KGSS).